FROZENSTORAGE CHARACTERISTICS OF CULTURED MACROBRACHIUM ROSENBERG/I (dE MAN) - BASU, S.; CHOUKSEY, M. K. (Journal of Indian Fisheries Association, 2016)
Cultured Macro brachium rosenbergii (Scampi, about 30 g each) in headlessshell-on form was individually quick frozen in a spiral freezer. The frozensamples were glazed and packed in polythene bags, which were further pac\{edin master carton and stored at - 18 oc. Samples were drawn at regularintervals and subjected to biochemical, bacteriological and organolepticanalysis to study its storage characteristics. The data on the above parametersshowed that the samples were in prime acceptable condition when storedupto 23 weeks. No appreciable change in colour and odour was noticed in theraw muscle. Mterwards, organoleptic evaluation of the cooked muscle revealedslight change in the flavour. Texture also appeared little tougher. Thesechanges in organoleptic characters were well supported by the biochemicalbacteriological changes in the muscle.Keywords : Storage characteristics, biochemical, bacterologicalorganoloptic